IMPLEMENTASI INTERNET OF THINGS (IoT) DENGAN PROTOKOL KOMUNIKASI MQTT PADA SISTEM KONTROL LAMPU RUANGAN - Makhrus, Moh. Ali; Makhrus, Moh Ali; Pradini, Risqy Siwi; Rikatsih, Nindynar (Universitas Pancasila, 2025)
The increasing need for automation of electronic devices encourages the use of Internet of Things (IoT) technology to improve energy efficiency, ease of control, and flexibility of access. This study designs and implements an IoT-based lighting control system using the Message Queuing Telemetry Transport (MQTT) protocol, which is efficient and lightweight in data communication. The system utilizes the NodeMCU ESP8266 microcontroller, the DS3231 Real Time Clock (RTC) module for automatic scheduling, and the Wi-Fi Manager for network configuration via a web interface without re-uploading code. Testing includes evaluating response time, bandwidth consumption, and connection stability when switching networks. The results show that the system has an average response time of 0.05–0.08 seconds and a minimum bandwidth consumption of 70 bytes per second. The system can also switch networks automatically without any disruption of function, making it a reliable and efficient solution for lighting control on a household, institutional, and commercial scale.